Tuberous sclerosis in a child - Sonawane, Vijay Baburao; Kotrashetti, V.; Bainade, Kapil; Vatkar, Amit; Bunde, Saili (International Journal of Contemporary Pediatrics, 2020)
Tuberous Sclerosis (TS) is the most common single gene disorder in children. It has an incidence of 1 in 5800 live births. It is an autosomal dominant genetic multisystemic disease characterized by hamartic development of many organs most notably the brain, heart, kidney, lungs and skin. It results from mutation of TSC1 and TSC2 gene coding for hamartin and tuberin respectively. Most of the newborns are asymptomatic. In infancy, seizures are the most common symptoms with a high incidence of infantile spasm while children between 2- 10 years neurological symptoms are most frequent with epilepsy, mental retardation and autism. Authors report a 4-year-old male child born of grade 3 consanguineous marriage presented with seizures in form of Infantile Spasm and Skin Lesions.